Соціально-економічна оцінка ефективності HR-технологій - Пілат, Юлія Дмитрівна (Чернівецький національний університет ім. Юрія Федьковича, 2023)
У роботі досліджено сутність та різновиди HR-технологій в управлінні персоналом. Подано методичні підходи до оцінки впливу цих технологій на ефективність управління організацією та визначено ключові індикатори ефективності їх використання на підприємстві. Проведено стратегічний аналіз розвитку ринку HR-технологій в Україні. Детально охарактеризовано цифрові HR-технології ТОВ «Епіцентр К» та визначено соціально-економічний ефект від впровадження HR-технологій на досліджуваному підприємстві. Запропоновано систематизувати інструменти цифровізації соціально-економічної оцінки HR-технологій та представлено впровадження системи індикаторів соціально-економічної оцінки на прикладі ТОВ «Епіцентр».
Socio-economic assessment of the effectiveness of HR technologies
The work examines the essence and types of HR technologies in HR management. Methodical approaches to assessing the impact of these technologies on the effectiveness of organizational management are presented and key indicators of the effectiveness of their use at the enterprise are determined. A strategic analysis of the development of the HR technology market in Ukraine was conducted. The digitized HR technologies of Epicenter K LLC are characterized in detail, and the socio-economic effect of the implementation of HR technologies at the investigated enterprise is determined. It is proposed to systematize the tools of socio-economic assessment digitalization of HR technologies and the implementation of the system of socioeconomic assessment indicators is presented on the example of "Epicentr" LLC.
Keywords: HR-технології; персонал; соціально-економічна оцінка; HR-метрики; цифрові інструменти; HRM-система; HR technologies; personnel; socio-economic assessment; HR metrics; digital tools; HRM system